2017
DOI: 10.1177/0003702817739908
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Total Reflection Fourier Transform Infrared (ATR FT-IR) Spectroscopy as an Analytical Method to Investigate the Secondary Structure of a Model Protein Embedded in Solid Lipid Matrices

Abstract: Protein drugs may encounter conformational perturbations during the formulation processing of lipid-based solid dosage forms. In aqueous protein solutions, attenuated total reflection Fourier transform infrared (ATR FT-IR) spectroscopy can investigate these conformational changes following the subtraction of spectral interference of solvent with protein amide I bands. However, in solid dosage forms, the possible spectral contribution of lipid carriers to protein amide I band may be an obstacle to determine con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…This research managed to observe the binding of a single phosphate on ATPase using a combination of ATR-FTIR spectroscopy with biospecific interaction analysis (BIA)-ATR biosensors, which allows the surface of the IRE to adsorb to a biomembrane [74]. ATR-FTIR spectroscopy has been used to investigate the secondary structure of denatured bovine serum albumin (BSA) alone and in a mixture with a native protein solid, which could be applied to investigate the solid-state formulation development process more thoroughly [75]. ATR-FTIR spectroscopy has also been used extensively to study proteins, in particular biopharmaceuticals, and exciting research has shown the potential applications of it to investigate and monitor changes effectively in PTMs and secondary structures.…”
Section: In-linementioning
confidence: 99%
“…This research managed to observe the binding of a single phosphate on ATPase using a combination of ATR-FTIR spectroscopy with biospecific interaction analysis (BIA)-ATR biosensors, which allows the surface of the IRE to adsorb to a biomembrane [74]. ATR-FTIR spectroscopy has been used to investigate the secondary structure of denatured bovine serum albumin (BSA) alone and in a mixture with a native protein solid, which could be applied to investigate the solid-state formulation development process more thoroughly [75]. ATR-FTIR spectroscopy has also been used extensively to study proteins, in particular biopharmaceuticals, and exciting research has shown the potential applications of it to investigate and monitor changes effectively in PTMs and secondary structures.…”
Section: In-linementioning
confidence: 99%
“…The main advantage of applying the IR spectroscopy for the analysis of protein structural characteristics is the independence of this method on the protein molecule size or the physical state of the sample. Not only the hydrated films or solid-state can be easily studied, but also the aqueous solution [12], organic solvents, detergents, micelles, and phospholipid membranes, all these states allow to study the native structure of the protein [13], as well as to assess the effect of the medium on the protein structure.…”
Section: Introductionmentioning
confidence: 99%
“…Since FT-IR is less sensitive to liquids than to solids, the protein secondary structure information was obtained by split-peak tting of the spectra results by origin soware. [31][32][33] As shown in Fig. 7, the peak positions shied and the absorbance changed aer the addition of AUR, indicating that the binding of AUR to XO affected the structure of XO protein.…”
Section: Conformational Changes Of Xo Upon Addition Of Aurmentioning
confidence: 86%